Community Skills Training in The Form of Innovation in Processing Young Papaya Fruit in Kuapan Village - Dede Permana; Nur Malasari Mala; Aulia Syafitri; Rafiq Aqil; Haden El Pasta; Muhammad Latif; Indah Wahyuni; Nurfadilla Nurfadilla; Asih Melindaj Sari; Fitri Nurdiana; Dika Guspita (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Kuapan village is one of the villages in The Mining district, Kampar Regency, the area reaches 8 km2 and the population is 3.858 people. The area of Kuapan Village consists of 5 hamlets. One of the natural resources owned by Kuapan Village is papaya fruit commodities. Considering that the plants in the yard and care are quite young, making papaya one of the plants that is very easy to find in Kuapan village. But unfortunately behind these advantages there are disadvantages of papaya trees. One of them, when bad weather arrives, sometimes many papaya trees fall. This causes many papaya fruits, especially still in an immature condition, to be thrown away by the community because they don't know what they want to process if they are in large quantities. Starting from this condition, it gave rise to the team's thought of holding a training program for making young papaya gut chips.The method of community empowerment is carried out with participatory methods. The target of the training was the Pkk of Kuapan Village as many as 20 people. This activity was carried out once in one training, but the team participated in monitoring and directing when the mothers of PKK members conducted a trial of re-making young papaya gut chips. This training activity for making young papaya gut chips went smoothly and conducively. The results of this activity include the Kuapan Village PKK being able to process young papaya which was once wasted and not used into culinary preparations in the form of young papaya intestine chips which can later become products that have a high selling price in the market. The existence of this training can increase the understanding of PKK members regarding the processing and utilization of young papaya fruit. The training implementation team will continue to provide assistance, monitor and evaluate the process of making products by participants